2019
DOI: 10.3847/2041-8213/ab01db
|View full text |Cite
|
Sign up to set email alerts
|

Crater Density Predictions for New Horizons Flyby Target 2014 MU69

Abstract: In preparation for the Jan 1/2019 encounter between the New Horizons spacecraft and the Kuiper Belt object 2014 MU69, we provide estimates of the expected impact crater surface density on the Kuiper Belt object. Using the observed crater fields on Charon and Pluto down to the resolution limit of the 2015 New Horizons flyby of those bodies and estimates of the orbital distribution of the crater-forming projectiles, we calculate the number of craters per unit area formed as a function of the time a surface on 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 28 publications
8
53
1
Order By: Relevance
“…We found that the large objects have a significant effect on long-term time scales, leading to a modest enhancement of the injection rate of new comets into the inner solar system. The reservoir requirements implied by our injection rate remain in broad agreement with recent reservoir estimations done from observations of the trans-Neptunian regions, as well as with those estimated from the analysis of cratering records on Pluto and 2014 MU 69 (Greenstreet et al 2015(Greenstreet et al , 2019Singer et al 2019).…”
Section: Introductionsupporting
confidence: 89%
“…We found that the large objects have a significant effect on long-term time scales, leading to a modest enhancement of the injection rate of new comets into the inner solar system. The reservoir requirements implied by our injection rate remain in broad agreement with recent reservoir estimations done from observations of the trans-Neptunian regions, as well as with those estimated from the analysis of cratering records on Pluto and 2014 MU 69 (Greenstreet et al 2015(Greenstreet et al , 2019Singer et al 2019).…”
Section: Introductionsupporting
confidence: 89%
“…Crater morphology varies with the impactor and target characteristics. The low and high velocity tails of the expected impact velocity distribution for Arrokoth reach down to a few m s -1 and as high as a few km s -1 , but the mode, ~300 m s -1 (5), is slow compared to primary cratering velocities on the surfaces of both icy and rocky bodies closer to the Sun, and is more typical of secondary cratering velocities on those bodies (85,86). These impacts often form craters with similar morphological characteristics to primary craters, although secondary craters are often shallower than the same size primary impact, and may be elongated in the direction radial to the primary crater.…”
Section: Supplementary Text Expected Impact Crater Morphologiesmentioning
confidence: 97%
“…The interior shape of a crater is expected to be bowl-like with a depth/diameter ratio typically not higher than ~0.2 (31). The predicted modal impact velocity onto Arrokoth is ~300 m s -1 (5), which is sufficient to form craters with typical morphologies (see Supplementary Text). In the case of Arrokoth, the lowest velocity impacts (≲ 20 m s -1 ) are unlikely to leave conspicuous depressions, but these impacts are expected to be a small fraction of the total (5).…”
Section: Pits and Cratersmentioning
confidence: 99%
See 2 more Smart Citations